Green Synthesis of Nanostructure CeO2 Using Tea Extract: Characterization and Adsorption of Dye from Aqueous Phase - Chengshun Liu; Xiyao Liu; Yilin Wu; Zhuotong Chen; Zhuanrong Wu; Shumao Wang; Hua Han; Zhenbang Xie; Yixuan Wang; Tzu-Hsing Ko (Bioinorganic Chemistry and Applications)
Nanostructure CeO2 powders were synthesized using tea waste extract as gel precursor. The as-prepared samples were characterized by thermogravimetric analyzer (TGA), X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy. Based on the TGA/DTG analysis, the intermediates of cerium chloride hydrates (CeCl3.4H2O and CeCl3.H2O) and cerium anhydrous (CeCl3) were produced, and the formation temperature of CeO2 was estimated to be 773 K. The cubic fluorite structure of CeO2 was detected to be the predominant species and was completely formed at the calcination temperature of 773K–1073 K with a crystal size between 8.8 and 11.4 nm based on the XRD measurement. Moreover, the main chemical state of ceria on the surface of the synthesized samples was confirmed to be tetravalent ceria by XPS. All samples show a strong Raman signal at a well-defined chemical shift of 463 cm−1 and a significant symmetry feature was observed, suggesting that the tetravalent ceria is the dominant species throughout the bulk sample. All the synthesized CeO2 calcined at different temperatures showed higher adsorption efficiency for Congo red (CR) compared with commercial CeO2. The adsorption efficiency maintained a steady state of more than 95% when the concentration of CR and adsorption temperature were varied in this study. The kinetic analysis showed that the second-order model was the appropriate model to interpret the adsorption behavior of synthesized CeO2. The calculated adsorption capacity derived from the second-order model is in good agreement with the experimental data. The isotherm analysis revealed that the Freundlich and D-R models fit well for the synthesized CeO2 and represent physisorption with a multilayer mechanism. The thermodynamic parameters, including the changes in Gibb’s free energy, enthalpy, and entropy, suggested that the adsorption of CR on the synthesized CeO2 sample was a spontaneous and endothermic process.